2001
DOI: 10.1259/bjr.74.877.740015
|View full text |Cite
|
Sign up to set email alerts
|

MRI in the diagnosis and treatment of suspected malignant spinal cord compression

Abstract: It remains unclear whether MRI is essential in all patients with suspected malignant spinal cord compression (MSCC), or whether some patients can be treated on the basis of plain radiographic findings and neurological examination. A prospective study was carried out of 280 consecutive patients with suspected MSCC, and the results of neurological examination plus plain radiographs were compared with MRI. 201 patients had MSCC (186 extradural, 5 intradural extramedullary and 10 intramedullary) and 11 patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 20 publications
1
38
0
2
Order By: Relevance
“…MRi is superior in imaging with high specificity and sensitivity, myeloma lesions appear as typical hypointense lesions in T1 sequences and hyperintense in T2 and STIR sequences [ 15,16]. out of 19 patients with uknown etiology the first manifestation of plasma cell neoplasm in the spine almost 3 / 4 findings were described as secondary metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…MRi is superior in imaging with high specificity and sensitivity, myeloma lesions appear as typical hypointense lesions in T1 sequences and hyperintense in T2 and STIR sequences [ 15,16]. out of 19 patients with uknown etiology the first manifestation of plasma cell neoplasm in the spine almost 3 / 4 findings were described as secondary metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…10,19 This seems plausible in our patient's case as the cauda equina, compared with other peripheral nerve roots, has a poorly developed epineurium and lacks a segmental blood supply, making it highly susceptible to injury. 17,20,21 The appearance of the cauda equina in our patient was unlikely to be a result of his 2004 pelvic radiation owing to the location of the nerve roots involved.…”
Section: Discussionmentioning
confidence: 86%
“…10 A retrospective study of 362 patients with suspected metastatic SCC identified 5 patients with neurological symptoms and thecal compression but no structural evidence of metastases. 19 No follow-up data for these patients is available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, MRI is the best method for the diagnosis of MESCC, because both sensitivity and specificity are more than 90% [17,18]. T1-and T2-weighted MRI sequences often provide adequate anatomical detail for diagnostic decisions.…”
Section: Discussionmentioning
confidence: 99%